Coordinated analysis of urban integrated energy-traffic networks based on real-world GPS data. (October 2018) - Yang, Tianyu; Guo, Qinglai; Lin, Chenhui; Xu, Luo; Sun, Hongbin
Abstract: The rapid growing scale of electric vehicles (EV) has brought benefit and impact on urban traffic network and the electric power system simultaneously by integrating these two systems together into a Cyber-Physical-Social System (CPSS) in energy. This paper presents a coordinated analysis method of the urban integrated energy-traffic network based on real-world GPS data from vehicles in Shenyang and Shenzhen, China. Case study shows that the integrated system will be affecting each other through the coupling interactions of EVs.